Factors Causing English Speaking Anxiety (ESA) in EFL Context: A Case Study among Post-Graduate Students in Indonesia - Titis Sulistyowati (Universitas Muhammadiyah Semarang, 2023)
This research presents quantitative and qualitative data relating to the effect of language anxiety on speaking motivation, the causes, and the way students cope with speaking anxiety. The participants of this research were 13 students from a post-Graduate class in the Language Education Department majoring in English Education at Universitas Negeri Semarang. They were adult EFL students who had acquired three languages or more. This research used semi-open-ended questionnaires to gather data from the participants. The study found that ESA adversely affects the student's speaking performance. Post-graduate students also experience it. The students feel uneasy, unconfident, nervous, and afraid of speaking English as a foreign language, affecting their speaking motivation and fluency during class presentations and discussions. Keywords: Speaking Motivation, EFL, and Adult Learners